Autorregulação emocional na perspectiva social cognitiva: uma revisão integrativa - TORQUATO, Jamille Gabriela da Silva (Universidade Metodista de Piracicaba, 2023)
Man is constituted as an autonomous subject who, according to the Cognitive So cial Theory, is able to self-regulate his behavior, motivations, emotions, among other aspects. This research aims to build an overview of national and international research on emotional self-regulation in the cognitive social perspective, through an integrative literature review, considering the period from 2008 to 2019; identifying what the authors have approached about this theme and pointing out possible gaps. With a quantitative, this study appropria ted a frequency analysis using the NodeXL software, which generated a graph with data of centrality measures adopted in order to highlight the most relevant constructs. The results pointed to five analyzed articles that presented the relevance of four constructs: Emotional intelligence; Emotional competence; Emotion regulation; Coping These data demonstrate that the literature has stated that the subject who is capable of self-regulating emotionally has satisfactory emotional intelligence, and is competent to face situations that can generate a negative emotional state. In addition, it is necessary to invest in programs that stimulate emotional competence in individuals to ensure effective management of emotions.